Inventory of Greenhouse Gas Emissions in the Energy Sector in Gili Iyang Island, Sumenep Regency Using the IPCC 2006 Method - Dianbudiyanto, Wahid; Fitriani, Nurina; Shalva, Rezhyta Nahatya; Fatmawati, Fatmawati; Isnadina, Dwi Ratri Mitha; Pratama, M Bagas Pramudya; Rahman, Danar Arifka; Nathanael, Rinaldy Jose; Hutama, Dio Alif (Journal of Sustainability Perspectives, 2025)
Global warming comes from many human activities, such as the burning of fossil fuels and the use of energy can produce Greenhouse Gases. The energy sector itself is the largest contributor of greenhouse gases in the world. This study aims to determine the greenhouse gas emissions produced in the energy sector on Gili Iyang Island. To be able to determine the greenhouse gas emissions produced in the energy sector on Gili Iyang Island, the IPCC 2006 calculation method was used. In this method, primary data is needed in the form of data on energy and fuel consumption activities of residents and secondary data in the form of the number of families on Gili Iyang Island. In the stationary source itself, CO2 gas emissions are produced at 1,438,259.9 Kg/Year, CH4 gas at 324.164 Kg/Year, and N2O gas at 12.486 Kg/Year. Meanwhile, moving sources produce CO2 gas emissions of 510,339.1052 Kg/Year, CH4 gas of 191.363 Kg/Year, and N2O gas of 20.969 Kg/Year. As for mitigation actions that can be taken based on its topography and climate, Gili Iyang Island has the potential to use solar panels and biogas as alternative energy and fuel sources to meet daily needs.